Metagenome sequencing and in silico gene discovery: From genetic potential to function - Anderson, Dominique Elizabeth (University of the Western Cape, 2012)
Doctor Scientiae - DSc In a previous study, metagenomic DNA extracted from Antarctic Dry Valley soils was used to construct a large contig bacterial shotgun fosmid library (Anderson, 2008). In the current study, clones were selected based on a functional screen for putative lipolytic enzymes, which incorporated tributyrin in agar screening plates. Clones were subsequently subjected to next-generation sequencing and bioinformatic analysis, which allowed for further investigation of a portion of the Antarctic metagenome. Assembly and annotation of the genetic data encoded on three fosmid clones allowed for the identification of the genes responsible for tributyrin hydrolysis. Furthermore, hypotheses relating to survival and adaptation to abiotic conditions prevalent in the extreme Antarctic environment were developed (Chapter 3). A cold adapted esterase was subsequently characterised and showed substrate preference for para-nitrophenyl propionate. The optimum temperature and pH for the enzyme, DEaseI was 25 ° C and 8.5, respectively. In addition, results indicated that DEaseI was sensitive to thermal inactivation (Chapter 4). Furthermore, in fosmid clone LD13, one particular ORF annotated as a Water HYpersensitity response protein, became the focus of further study. When sub-cloned into a heterologous host, both ionic and osmotic stress tolerance was observed in vivo. The protein also exhibited a cryoprotective function in vitro, preventing cold denaturation of malate dehydrogenase during cycles of freeze-thaw (Chapter 5). This study demonstrates the value of combinatorial in silico and ‘-omic’ based techniques for the discovery and functional characterisation of potentially novel genes from bacteria which inhabit Antarctic Dry Valley soils.